THE REPRESENTATION OF THE HISTORY OF BUKHARA JEWS IN THE SCHOLARLY LITERATURE OF THE 20TH–21ST CENTURIES - Botirov Sarvar Bahrom ugli (Western European Studies, 2025)
this article explores the representation of Bukhara Jews in scholarly literature from the 20th to the 21st centuries. It examines the historical narrative surrounding this unique community, highlighting its cultural, social, and economic contributions to the broader tapestry of Jewish history. By analyzing various academic sources, the article aims to identify prevailing themes, biases, and gaps in the scholarship. Additionally, it reflects on how changes in geopolitical landscapes and academic discourse have influenced the portrayal of Bukhara Jews over time. Through this exploration, the article contributes to a deeper understanding of minority histories and their significance within the larger framework of Jewish studies
Keywords: Jewish history; Cultural representation; Minority studies